Mechanical and Thermal Properties of Poly(lactid acid) Bamboo Fiber Composites - Nanang Masruchin; Sasa S Munawar; Subyakto Subyakto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The effect of natural fiber, unbleached bamboo fibers (BF) on poly(lactid acid) (PLA) composite by means mechanical and thermal properties on the presence of plasticizer, triacetine was investigated. Wet processing was chosen by dissolving PLA on dicloromethane then BF with different fiber loading i.e 30, 40 and 50% were added. Thermal properties were analyzed by Differential Scanning Calorimetry (DSC) and Thermogravimetry (TGA). The result showed that BF could increase the flexural strength and modulus of pure PLA by increasing the fiber loading. Moreover, it decreased at high fiber content (50%) due to the agglomeration of the fiber; however, the mechanical properties are still better than those of neat PLA. The best performances were shown by increasing the strength and modulus by 49.55% and 122.71% at 40% fiber content, respectively. DSC showed that fiber loading and plasticizer decreased glass transition temperature (Tg), meanwhile melting temperature (Tm) not significantly influence. Beside that TGA analyze showed that PLA/BF 60/40 composite start to decompose at 230 oC. Microscopic surface fracture of composites revealed by Scanning Electron Microscopy (SEM) showed fibers pull out, may due to lack of fiber-matrix bonding.Key words: bamboo fibers, composites, DSC, poly(lactic acid).